Appraisal of surface water quality in vicinity of industrial areas and associated ecological and human health risks: a study on the Bangshi river in Bangladesh. (2nd October 2022) - Latif, Mahmuda Binte; Khalifa, Md. Abul Kalam; Hoque, Mir Md. Mozammal; Ahammed, Md. Shakir; Islam, Alisha; Kabir, Md. Humayun; Tusher, Tanmoy Roy
Abstract: Anthropogenic interventions along the river of the developing countries like Bangladesh have resulted in water quality deterioration and significant environmental and human health hazards. This study aimed to evaluate the water quality of the Bangshi river subjected to the anthropogenic activities, especially resulting from industrial and domestic activities, and to decipher probable ecological and human health risks of river water during the high-demand period. Thus, surface water samples were collected from six sampling stations along the mainstream of the river, and thirteen different water quality parameters were investigated. Weighted arithmetic water quality index (WQI) was employed to evaluate the suitability of river water for drinking and fisheries purposes, whereas the hazard quotient (HQ), hazard index (HI), and ecological risk index (ERI) were used to measure the potential human health and ecological risks derived from polluted river water. The results exhibited that some water quality parameters (EC, DO, and Fe) exceeded the permissible limits at certain sampling stations, indicating the influence of anthropogenic interventions on the river water quality at those areas. The WQI analysis revealed that the river water is unsuitable for drinking and/or fisheries and needs to be treated properly prior to utilization. Principal component analysis (PCA) extracted four principal components accounted for 95.84% of the total variance, suggesting both natural and anthropogenic sources of pollution. The HQ and HI values (<1) suggested low possibility of causing a potential health risks via oral and dermal exposures, while the ERI values (1.79–7.27) also indicated low ecological risks in the study area. Unhealthy human activities that expose this waterbody to pollutants should be stopped, and eco-friendly waste and effluent treatment methods should be used instead.